EVALUATION OF THE QUALITY ASSURANCE SYSTEM FOR HERBAL PRODUCT MANUFACTURING AT PT. X BASED ON GOOD TRADITIONAL MEDICINE MANUFACTURING PRACTICES (CPOTB) - Putu Bagus Diva Yogiswara; Putu Ika Divta Candra Devi; Tesalonika Ester Selaindoong; Lisa Susana Lokollo; Putu Oka Samirana (Journal Pharmaceutical Science and Application, 2026)
Background: Herbal products require a proper quality assurance system to ensure consistent manufacturing and compliance with safety and quality standards. The quality assurance system is crucial for overseeing the entire production process, starting from the acquisition of raw materials to the distribution of finished products. Objective: This research aims to assess the implementation of a quality assurance system in the manufacturing of herbal products at PT. X based on CPOTB. Methods: This study employed a qualitative descriptive approach using a case study methodology. Data were collected through observations, interviews, and document reviews, which included standard operating procedures, batch production records, testing documents, equipment logbooks, and quality control records. The assessment focused on the quality management system, raw material oversight, staff, infrastructure and machinery, manufacturing methods, warehousing, and record-keeping. Results: The findings indicated that PT. X has established a cohesively integrated quality assurance system by fostering collaboration between the QA and QC divisions, despite facing challenges related to dual functional roles in the absence of a separate R&D department. Cross-contamination risks are addressed from both facility and production perspectives through the implementation of a structural three-zone workflow (Black, Green, and Gray Areas), supported by integrated HEPA filtration and Reverse Osmosis (RO) water systems. Additionally, quality control in the industry is rigorously maintained through strict adherence to instrument logbook regulations, effective batch-tracking methods for addressing complaints and product recalls, and a thorough and organized documentation system. Conclusion: PT. X requires strategic enhancements in structural aspects concerning personnel dual roles and the modernization of equipment. However, its comprehensive documentation, standardized internal audits, and strong environmental controls indicate that the facility's quality management aligns effectively. Keywords: CPOTB; Herbal preparations; Quality Assurance; Documentation; Quality system